2002
DOI: 10.1093/humrep/17.8.2089
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations in 4224 children conceived after IVF

Abstract: The small increase in overall congenital malformations observed in the IVF children appears to be attributable to differences in maternal characteristics and not to any aspect of the IVF procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 30 publications
2
79
1
9
Order By: Relevance
“…The details of the meta-analysis-including the literature search, the study selection and the data extraction processes-are described there. We found 19 studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] for inclusion in the meta-analysis and found that ART increased the risk of MM with an odds ratio of 1.29 (95% CI 1.01-1.67). Our major conclusion was that the risk we found may be inflated by the fact that none of the studies used the most appropriate control group, namely subfertile couples conceiving spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the meta-analysis-including the literature search, the study selection and the data extraction processes-are described there. We found 19 studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] for inclusion in the meta-analysis and found that ART increased the risk of MM with an odds ratio of 1.29 (95% CI 1.01-1.67). Our major conclusion was that the risk we found may be inflated by the fact that none of the studies used the most appropriate control group, namely subfertile couples conceiving spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing numbers of infants born following IVF, a number of issues related to these infants have come to the fore in medical literature. These issues include increased infant mortality rates, failure to thrive, increased morbidity in early childhood [1], increased risk of congenital anomalies [2][3][4] and increased incidence of adverse neurological sequelae [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a Dutch registry study, major birth defects in 4224 ART children were compared to 314,605 naturally conceived children [34]. Major birth defect rates were 3.2 % and 2.7 % for ART and naturally conceived children respectively, but the significance of the difference disappeared after adjustment for maternal age, parity and ethnicity.…”
Section: Congenital Malformationsmentioning
confidence: 99%